2013
DOI: 10.3390/su5020456
|View full text |Cite
|
Sign up to set email alerts
|

Building Damage and Business Continuity Management in the Event of Natural Hazards: Case Study of the 2004 Tsunami in Sri Lanka

Abstract: Abstract:The Sumatra Earthquake and Indian Ocean Tsunami event on the 26 December 2004 has provided a unique and valuable opportunity to evaluate the performance of various structures, facilities and lifeline systems during the tsunami wave attacks. There are especially meaningful observations concerning the structural changes due to the tsunami forces, which open up a wide area of research to develop the mitigation procedure. The business restoration process of business companies in terms of buildings, facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Populations have decreased in regions of flood exposure in the USA, such as New Orleans, USA, after Hurricane Katrina (see Figure 3A), consistent with other studies showing decreases in urbanization and population exposure in modeled FEMA flood zones in the coastal US 48,49 . In Sri Lanka, a decrease in the proportion of population exposed to floods is partially due to policy changes after the 2004 tsunami requiring residents to relocate at least 100 m from the shoreline, which displaced up to 500,000 people 50,51 .…”
Section: Past Proportion Of Population Exposed To Large Floods: 2000-...mentioning
confidence: 99%
“…Populations have decreased in regions of flood exposure in the USA, such as New Orleans, USA, after Hurricane Katrina (see Figure 3A), consistent with other studies showing decreases in urbanization and population exposure in modeled FEMA flood zones in the coastal US 48,49 . In Sri Lanka, a decrease in the proportion of population exposed to floods is partially due to policy changes after the 2004 tsunami requiring residents to relocate at least 100 m from the shoreline, which displaced up to 500,000 people 50,51 .…”
Section: Past Proportion Of Population Exposed To Large Floods: 2000-...mentioning
confidence: 99%
“…For example, Lanka et al [10] reported that the Batticaloa cyclone of 1978, considered one of the most disastrous cyclones to have hit Sri Lanka, resulted in widespread destruction in the study area as a result of the heavy rain and storm surges it caused. The Oluvil region was severely impacted by the 2004 tsunami, which was another catastrophic disaster to strike the area [11][12][13]. Additionally, the area is susceptible to storm surges resulting from frequent depressions within the Bay of Bengal [14].…”
Section: Introductionmentioning
confidence: 99%